Positive electrode material and preparation method thereof, positive electrode plate and lithium ion battery
By forming a multi-layer structure of layered substrate, replacing layered substrate, heterojunction layer and perovskite structure layer on the surface of the positive electrode material of lithium-ion battery, the problems of irreversible oxygen loss and transition metal dissolution at high voltage are solved, and the problems of significant improvement of the problem of high voltage are significantly improved. The battery cycle stability and safety performance are provided.
Patent Information
- Application Number
- CN202411339641.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing lithium-ion battery positive electrode materials have irreversible oxygen loss at high voltage, resulting in structural deterioration, capacity attenuation and poor safety. The existing surface modification methods are difficult to solve problems such as gas production and transition metal dissolution at the same time, which affects battery performance and life.
Using a positive electrode material including layered substrates, replace layered substrate layers, heterojunction layers and perovskite structural layers, a gradient heterojunction layer is formed through spray coating technology to improve high voltage stability and enhance ion conductivity and reduce Oxygen output reaction impedance.
It significantly improves the cycle stability and safety performance of the positive electrode material at high voltage, achieves low gas production, low impedance and high voltage stability, and extends the service life of lithium-ion batteries.
Smart Images

Figure CN119297228A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of positive electrode materials for lithium batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art
[0002] With the rapid development of economy, people's demand for energy is gradually increasing. Layered oxide positive electrode materials have high capacity, discharge platform and compaction density. They are one of the most thoroughly studied and widely used commercial lithium-ion battery positive electrode materials.
[0003] Taking lithium cobalt oxide as an example, its energy density can be improved by increasing the cut-off working voltage and compaction density. In the existing technology, the compaction density of lithium cobalt oxide has reached 4.2g / cm³, and there is limited room for improvement; the only means of further optimization is to improve the energy density by increasing the cut-off voltage. However, as the cut-off voltage of lithium-ion batteries increases, the performance of lithium-ion batteries deteriorates significantly. Lithium cobalt oxide may undergo a structural phase transition of O3→H1-3→O1 under high voltage, resulting in a sharp collapse of the lattice. Since the 3d energy band of Co overlaps with the 2p energy band of O to a large extent, Fm is located on the 2p energy band of O in the highly de-lithiated state, resulting in oxidation of the lattice oxygen of the positive electrode material and oxygen release of the material, that is, irreversible oxygen loss occurs under high voltage, causing further collapse of the lithium cobalt oxide structure, further exacerbating the structural deterioration and capacity attenuation of lithium cobalt oxide during the cycle, making the thermal stability and safety of the lithium cobalt oxide positive electrode material much worse, thereby affecting the performance and service life of lithium-ion batteries.
[0004] Taking ternary positive electrode materials as an example, ternary positive electrode materials are in direct contact with the electrolyte. The surface of the positive electrode material is easily corroded by the electrolyte, causing the dissolution of transition metals such as Co, Mn, and Ni. The original layered structure is destroyed, which will lead to a series of safety problems.
[0005] Modifying the surface of lithium-ion cathode materials can effectively reduce the contact area between the cathode materials and the electrolyte, reduce the dissolution amount of transition metals, and improve the structural stability and cycling performance. Common surface modification methods include coating metal oxides, phosphates, ion-electron dual conductors, etc. Metal oxides such as ZnO, A12O3, TiO2, etc. These materials have stable structures and will not react with the electrolyte, playing a role in protecting the cathode materials. However, most oxides are electron-insulating, and the coating will increase the electron conductivity impedance of the cathode materials, reduce the capacity utilization, and have a limited improvement in gas generation. Metal phosphates such as AlPO4, Li3PO3, LiMgPO4, etc. Coating the cathode materials with these materials is beneficial to improve their capacity retention rate, but it cannot improve the corrosion of the electrolyte on the cathode surface at high voltages, and the protection ability is limited at high voltages. Coating ion-electron dual conductors usually refers to coating other cathode materials, such as ternary materials, lithium iron phosphate, lithium manganate, etc. These materials are either unstable at high voltages or have the risk of insufficient energy density, and the risk of gas generation still exists at high voltages.
[0006] In view of this, the present invention is specifically proposed. Summary of the Invention
[0007] In view of the fact that the existing coating methods are difficult to comprehensively solve various problems of the cathode materials, such as gas generation and transition metal dissolution, while maintaining good electrochemical performance of the cathode materials, the present invention provides a cathode material, a preparation method thereof, a cathode electrode sheet and a lithium-ion battery, aiming to provide a coated and modified cathode material with high ionic conductivity, low gas generation amount and excellent cycle stability.
[0008] The present invention is implemented as follows: In a first aspect, the present invention provides a cathode material, which includes a layered matrix, a substituted layered matrix layer, a heterojunction layer and a perovskite structure layer.
[0009] The layered matrix has a chemical general formula Li a M 1-b M′ b O2, where 0.98 ≤ a ≤ 1.02, 0 < b ≤ 0.1, M is at least one of Ni, Co and Mn; M′ is at least one of Ba, La, Ti, Zr, V, Nb, Cu, Mg, B, Sr, Al, Sc, Y, Ga, Zn, W, Mo, Si, Sb and Ca; The substituted layered matrix layer is distributed in a direction away from the layered matrix and is connected to the layered matrix. The substituted layered matrix layer has a layered structure different from that of the layered matrix. The substituted layered matrix layer has a chemical general formula Li a-x C x M 1-b M′ bO2, wherein 0<x≤0.3; C is metal element A or / and metal element B; The heterojunction layer is distributed on the surface of the substituted layered matrix layer away from the layered matrix, and is connected to the substituted layered matrix layer, and the heterojunction layer includes at least one of a spinel structure and a rock salt phase structure; The perovskite structure layer is distributed on the surface of the heterojunction layer away from the layered matrix and is connected to the heterojunction layer. The perovskite structure layer has a general chemical formula ABO3, wherein A and B are both metal elements.
[0010] In some embodiments of the present invention, the repose angle of the positive electrode material is ≤55°. Preferably, the repose angle of the positive electrode material is 30°~50°.
[0011] In some embodiments of the present invention, the Li a-x C x M 1-b M′ b In O2, the value of x is 0<x≤0.1.
[0012] In some embodiments of the present invention, the total mass of element A and element B in the positive electrode material is less than 5% of the total mass of the positive electrode material; preferably, the total mass of element A and element B in the positive electrode material is less than 3% of the total mass of the positive electrode material.
[0013] In some embodiments of the present invention, A in ABO3 is at least one of Pb, Na, Sn, Sr, K, Ca, Ba, Pr, Ln, Sm, Gd and La; B is at least one of Ti, Mg, Y, Zn, Fe, Ta, Mn, Co, Ni, Mo, Nb, W and Al.
[0014] When the M element in the layered matrix of the positive electrode material is the same element as the B element in the perovskite structure layer, the chemical state of the same element in the layered matrix is different from the chemical state in the perovskite structure layer. The chemical state refers to the lattice position of the element and its combination state with atoms of other elements.
[0015] In some embodiments of the present invention, the median particle size Dv50 of the positive electrode material is 12 to 18 μm; In some embodiments of the present invention, the thickness of the substituted lamellar matrix layer is less than 50 nm; In some embodiments of the present invention, the thickness of the heterojunction layer is less than 10 nm; In some embodiments of the present invention, the thickness of the perovskite structure layer is less than 10 nm.
[0016] In a second aspect, the present invention provides a method for preparing the positive electrode material of any of the above embodiments, comprising the following steps: Prepare positive electrode active material; prepare mixed solution of source A and source B; Spraying the mixed solution on the surface of the positive electrode active material in a stirred state, and obtaining a spray-coated positive electrode material after drying; The spray-coated positive electrode material is sintered and then crushed to obtain the positive electrode material.
[0017] In some embodiments of the present invention, the method for preparing the positive electrode active material comprises the following steps: mixing a lithium source, an M source and an M′ source, calcining the mixture, and crushing the mixture to obtain the positive electrode active material.
[0018] In some embodiments, the calcination temperature is 600-1100° C., preferably 800-1090° C.; the calcination time is 5-15 h, preferably 7-14 h.
[0019] In some embodiments, the primary particles of the positive electrode active material have a particle size of 2 to 25 μm; In some embodiments, the lithium source is at least one of lithium carbonate, lithium hydroxide, lithium acetate and lithium oxalate; In some embodiments, the M source is at least one of an oxide or hydroxide containing M; the M is at least one of Ni, Co and Mn; preferably, the M source is at least one of cobalt tetroxide, cobalt oxyhydroxide, cobalt hydroxide, nickel cobalt manganese oxide, nickel cobalt manganese hydroxide, manganese hydroxide, nickel hydroxide, nickel oxide and manganese oxide.
[0020] In some embodiments, the M′ source is at least one of an oxide, hydroxide, acetate, carbonate, and basic carbonate containing M′; and the M′ is at least one of Ba, La, Ti, Zr, V, Nb, Cu, Mg, B, Sr, Al, Sc, Y, Ga, Zn, W, Mo, Si, Sb, and Ca.
[0021] In some embodiments of the present invention, the A source is at least one of acetate, carbonate and basic carbonate containing A, and the A is at least one of Pb, Na, Sn, Sr, K, Ca, Ba, Ln, Pr, Sm, Gd and La.
[0022] In some embodiments of the present invention, the B source is at least one of acetate, carbonate and basic carbonate containing B, and the B is at least one of Ti, Mg, Y, Zn, Fe, Ta, Mn, Co, Ni, Mo, Nb, W and Al.
[0023] In some embodiments of the present invention, the mixed solution is an aqueous solution of source A and source B.
[0024] In some embodiments of the present invention, the molar ratio of element A to element B in the mixed solution is (1~1.1): (1~1.1).
[0025] In some embodiments of the present invention, the mixed solution is sprayed on the surface of the aluminum source and the positive electrode active material in a stirred state, and after drying, a spray-coated positive electrode material is obtained.
[0026] In some embodiments, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide, and aluminum oxyhydroxide.
[0027] In some embodiments of the present invention, the stirring speed is 300-1500 r / min; In some embodiments of the present invention, the spraying time is 10 to 60 minutes; In some embodiments of the present invention, the drying temperature is 40-150° C., preferably 40° C.; the drying time is 0.5-3 h, preferably 0.5 h.
[0028] In some embodiments of the present invention, the sintering temperature is 350-700°C, preferably 550°C; the sintering time is 2-10h, preferably 4h; In some embodiments of the present invention, the crushing adopts at least one of a vibrating screen, a mechanical mill, and a jet mill.
[0029] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material obtained according to any one of the above embodiments.
[0030] In a fourth aspect, the present invention provides a lithium-ion battery, comprising the above-mentioned positive electrode plate, as well as a negative electrode plate, an electrolyte and a separator.
[0031] In a fifth aspect, the present invention provides an electronic device comprising the above-mentioned lithium-ion battery.
[0032] The present invention has the following beneficial effects: (1) The present invention provides a surface-coated modified positive electrode material, which includes a layered matrix, a substituted layered matrix layer, a heterojunction layer and a perovskite structure layer. The heterojunction layer is a gradient heterojunction with spinel or / and rock salt phase, which can improve the phase interface, alleviate the irreversible oxygen loss problem of the positive electrode material under high voltage, and make the positive electrode material have better high voltage stability during the cycle process, thereby enabling the lithium ion battery to achieve a high voltage cycle capacity retention rate; in addition, the perovskite structure coating layer, as a fast ion conductor, has the characteristics of high electronic conductivity, high lithium ion conductivity and low oxygen ion conductivity, which significantly improves the OER (solid phase oxygen production reaction) reaction overpotential on the surface of the material, and can achieve reversible storage of high-valent oxygen in its oxygen vacancies under high voltage, thereby significantly improving the cycle stability of the layered oxide positive electrode material under high voltage. Therefore, the positive electrode material with the above characteristics provided by the present invention has the advantages of low gas production, low impedance, excellent cycle performance and safety performance, and good high-voltage stability.
[0033] (2) The present invention provides a method for preparing a positive electrode material. The present invention sprays a mixed solution containing source A and source B required for the perovskite structure on the surface of the positive electrode active material. The metal ions in the mixed solution are exchanged with the lithium ions in the positive electrode active material at a certain temperature, and the lithium ions are partially replaced to the surface layer, thereby forming a substituted layered matrix layer. The positive electrode material is further sprayed and coated, and a heterojunction layer and a perovskite structure layer are sequentially formed on the surface of the substituted layered matrix layer through sintering, thereby forming a structure of a layered matrix, a substituted layered matrix layer, a heterojunction layer, and a perovskite structure layer. The preparation method of the present invention is simple, and can effectively control the degree of ion exchange, avoiding excessive lithium ion loss leading to a decrease in capacity. In addition, the prepared perovskite structure layer is evenly distributed on the surface of the positive electrode material, and the equipment is simple, the process flow is small, and it has a good industrial prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 This is a SEM image of the positive electrode material prepared in Example 1; Figure 2 This is a SEM image of the positive electrode material prepared in Example 5; Figure 3 This is a SEM image of the positive electrode material prepared in Comparative Example 1; Figure 4 This is a SEM image of the positive electrode material prepared in Comparative Example 10; Figure 5 This is the TEM image of the positive electrode material prepared in Example 5. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0037] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0038] Reference to "embodiment" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments.
[0039] In the embodiment of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0040] In addition, the character “ / ” in this article generally indicates that the previous and next associated objects are in an “or” relationship.
[0041] In the embodiments of the present application, the meaning of "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multi-layer" refers to more than two layers (including two layers), unless otherwise clearly specified and limited.
[0042] In the embodiments of the present application, "at least one" means one or more than one.
[0043] In the embodiments of the present application, the orientations or positional relationships indicated by the technical terms "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", etc. are based on the orientations or positional relationships shown in the drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed in a specific orientation, etc., and cannot be understood as limiting the embodiments of the present application. Those skilled in the art can understand the specific meanings of the above terms in the embodiments of the present application according to specific circumstances.
[0044] In a first aspect, the present invention provides a cathode material, which includes a layered matrix, a substituted layered matrix layer, a heterojunction layer, and a perovskite structure layer.
[0045] The layered matrix has a chemical general formula Li a M 1-b M′ b O2, where 0.98 ≤ a ≤ 1.02, 0 < b ≤ 0.1, M is at least one of Ni, Co, and Mn; M′ is at least one of Ba, La, Ti, Zr, V, Nb, Cu, Mg, B, Sr, Al, Sc, Y, Ga, Zn, W, Mo, Si, Sb, and Ca; The substituted layered matrix layer is distributed in a direction away from the layered matrix and is connected to the layered matrix. The substituted layered matrix layer has a layered structure different from that of the layered matrix; the substituted layered matrix layer has a chemical general formula Li a-x C x M 1-b M′ b O2, where 0 < x ≤ 0.3, preferably 0 < x ≤ 0.1; C is metal element A or / and metal element B; The heterojunction layer is distributed on the surface of the substituted layered matrix layer in a direction away from the layered matrix and is connected to the substituted layered matrix layer. The heterojunction layer includes at least one of a spinel structure and a rock salt phase structure; The perovskite structure layer is distributed on the surface of the heterojunction layer in a direction away from the layered matrix and is connected to the heterojunction layer. The perovskite structure layer has a chemical general formula ABO3, where both A and B are metal elements.
[0046] The lithium content of the cathode material provided by the present invention gradually decreases along the directions of the layered matrix, the substituted layered matrix layer, the heterojunction layer, and the perovskite structure layer.
[0047] During the high-voltage lithium deintercalation state of the cathode material, lattice oxygen oxidation is likely to occur to generate gas. On the one hand, it causes the crystal structure of the cathode material to collapse, resulting in capacity attenuation; on the other hand, there are relatively large potential safety hazards, and the accumulation of gas will cause the battery to explode. In addition, the cathode material is in direct contact with the electrolyte, and the surface of the cathode material is easily corroded by the electrolyte, resulting in the dissolution of transition metals such as Co, Mn, and Ni. Surface coating of the cathode material can partially improve the above problems, but it may also cause problems such as capacity decline and impedance increase.
[0048] The positive electrode material provided by the present invention contains a heterojunction layer, which is a gradient heterojunction with spinel and / or rock salt phases, and can improve the phase interface between the substituted layered matrix layer, the heterojunction layer, and the perovskite structure layer, alleviate the irreversible oxygen loss problem of the positive electrode material under high voltage, so that the positive electrode material has better high-voltage stability during the cycle process, thereby enabling the lithium-ion battery to achieve a cycle capacity retention rate under high voltage; in addition, the perovskite structure coating layer, as a fast ion conductor, has the characteristics of high electronic conductivity, high lithium ion conductivity and low oxygen ion conductivity, significantly improves the OER (solid phase oxygen production reaction) reaction overpotential on the material surface, and can achieve reversible storage of high-valent oxygen in its oxygen vacancies under high voltage, thereby significantly improving the cycle stability of the layered oxide positive electrode material under high voltage.
[0049] Therefore, the positive electrode material with the above characteristics provided by the present invention has the advantages of low gas production, low impedance, excellent cycle performance and safety performance, and good high-voltage stability.
[0050] In some embodiments of the present invention, the repose angle of the positive electrode material is ≤55°. Preferably, the repose angle of the positive electrode material is 30°~50°.
[0051] The angle of repose can reflect the coating uniformity of the positive electrode material. The higher the coating uniformity, the smaller the interaction force between the particles, that is, the smaller the friction between the material particles, the greater the fluidity of the material particles, and the smaller the angle of repose.
[0052] The positive electrode material provided by the present invention has a suitable repose angle, and the perovskite structure layer on the outer surface of the positive electrode material is a uniform coating layer. From the scanning electron microscope (SEM) image, it can be observed that the coating structure of the positive electrode material includes a film-like coating and a small amount of island-like coating, and the uniformity is good; good coating uniformity is conducive to reducing interface side reactions, reducing gas production, improving structural stability, and improving cycle stability.
[0053] Layered matrix Li a M 1-b M′ b O2 undergoes a replacement reaction with the metal salt solution. At this time, part of the Li a M 1-b M′ b O2 as the main body does not react and remains in an ordered layer; while Li a M 1-b M′ b There is Li on the surface of O2 + Loss, Li + The lost vacancies are replaced by some metal C ions in the metal salt solution, and the resulting Li a-x C x M 1-b M′ bO2 layer.
[0054] If the mass percentage of C is too high, it will cause excessive lithium loss and a decrease in specific capacity; if the mass percentage of C is too low, the lithium replacement rate will be too low, resulting in a decrease in the effect of inhibiting gas production.
[0055] In some embodiments of the present invention, the total mass of element A and element B in the positive electrode material is less than 5% of the total mass of the positive electrode material; preferably, the total mass of element A and element B in the positive electrode material is less than 3% of the total mass of the positive electrode material.
[0056] The content of element A and element B is too low, indicating that the fewer the perovskite structure layers, the less the coating amount, which will reduce the gas production inhibition effect and cycle stability; the content of element A and element B is too high, and the degree of ion exchange with the layered matrix is also higher, resulting in Li + The loss is large, which leads to a decrease in the specific capacity of the positive electrode material.
[0057] In some embodiments of the present invention, A in ABO3 is at least one of Pb, Na, Sn, K, Ca, Ba, Sr, Ln, Pr, Sm, Gd and La; B is at least one of Ti, Mg, Y, Zn, Fe, Ta, Mn, Co, Ni, Mo, Nb, W and Al.
[0058] When the M element in the layered matrix in the positive electrode material and the B element in the perovskite structure layer are the same element, the chemical state of the same element in the layered matrix is different from the chemical state in the perovskite structure layer.
[0059] In some embodiments of the present invention, the median particle size Dv50 of the positive electrode material is 12-18 μm; In some embodiments of the present invention, the thickness of the substituted lamellar matrix layer is less than 50 nm; In some embodiments of the present invention, the thickness of the heterojunction layer is less than 10 nm; In some embodiments of the present invention, the thickness of the perovskite structure layer is less than 10 nm.
[0060] The positive electrode material provided by the present invention has a multilayer structure, wherein the thicknesses of the substituted layered matrix layer, the heterojunction layer, and the perovskite structure layer are all relatively small, so the specific capacity of the positive electrode material does not decrease due to coating modification and still maintains a relatively high specific capacity.
[0061] In a second aspect, the present invention provides a method for preparing the positive electrode material of any of the above embodiments, comprising the following steps: Prepare positive electrode active material; prepare mixed solution of source A and source B; Spraying the mixed solution on the surface of the positive electrode active material in a stirred state, and obtaining a spray-coated positive electrode material after drying; The spray-coated positive electrode material is sintered and then crushed to obtain the positive electrode material.
[0062] The present invention applies a mixed solution containing source A and source B to the surface of the positive electrode active material by spraying, which is beneficial to control the degree of ion exchange between the positive electrode material and the mixed solution, and obtains a substituted layered matrix layer (Li a-x C x M 1-b M′ b O2); In addition, the thickness of the obtained substituted layered matrix layer can be controlled by spraying, making it thinner, so as to avoid too much influence on the specific capacity of the positive electrode material. Furthermore, the mixed solution is sprayed on the positive electrode surface under stirring, so that the elements A and B are evenly distributed on the surface of the positive electrode material, so that the perovskite structure layer on the surface of the positive electrode material is evenly distributed, and the coating uniformity and effectiveness are greatly improved.
[0063] It should be noted that the chemical formula of the positive electrode active material of the present invention is Li a M 1-b M′ b O2, by spraying a mixed solution on its surface, part of the positive electrode active material undergoes ion exchange to obtain the layered matrix layer and the original substituted layered matrix layer, and after the sprayed coated positive electrode material is sintered, part of the original substituted layered matrix layer reacts to form a heterojunction layer, thereby obtaining the substituted layered matrix layer and the heterojunction layer.
[0064] Ion exchange is a liquid-solid phase reaction process involving the diffusion of substances in the liquid and solid phases. The mixed solution is evenly sprayed on the surface of the positive electrode material by spraying and stirring. The metal ions in the mixed solution are exchanged with the lithium in the positive electrode active material at a certain temperature, and part of the lithium ions are replaced in the surface layer, thereby forming a replaced layered matrix layer.
[0065] Further spray coating of the positive electrode material is performed through sintering to sequentially form a heterojunction layer and a calcium iron ore structure layer on the surface of the replaced layered matrix layer, thereby forming a structure of a layered matrix, a replaced layered matrix layer, a heterojunction layer, and a calcium iron ore structure layer. Among them, the heterojunction layer is a layered matrix (Li a-x C x M 1-b M′ b O2) is reacted with a part of the perovskite structure (ABO3) at high temperature, and the heterojunction layer is a gradient heterojunction with spinel and / or rock salt phase.
[0066] The preparation method of the invention is simple, the equipment is simple, the process flow is less, and it has good industrialization prospect.
[0067] In some embodiments of the present invention, the method for preparing the positive electrode active material comprises the following steps: mixing a lithium source, an M source, and an M′ source, calcining the mixture, and crushing the mixture to obtain the positive electrode active material.
[0068] It should be noted that the preparation method of the positive electrode active material described in the present invention is not limited to the above-mentioned solid phase method, and can also adopt salt decomposition method, coprecipitation method, sol-gel method, hydrothermal method, reverse emulsion method, template method and other methods.
[0069] In some embodiments, the calcination temperature is 600-1100° C., preferably 800-1090° C.; the calcination time is 5-15 h, preferably 7-14 h.
[0070] In some embodiments, the primary particles of the positive electrode active material have a particle size of 2 to 25 μm; In some embodiments, the lithium source is at least one of lithium carbonate, lithium hydroxide, lithium acetate and lithium oxalate; In some embodiments, the M source is at least one of an oxide or hydroxide containing M; the M is at least one of Ni, Co and Mn; preferably, the M source is at least one of cobalt tetroxide, cobalt oxyhydroxide, cobalt hydroxide, nickel cobalt manganese oxide, nickel cobalt manganese hydroxide, manganese hydroxide, nickel hydroxide, nickel oxide and manganese oxide.
[0071] In some embodiments, the M′ source is at least one of an oxide, hydroxide, acetate, carbonate and basic carbonate containing M′; and the M′ is at least one of Ba, La, Ti, Zr, V, Nb, Cu, Mg, B, Sr, Al, Sc, Y, Ga, Zn, W, Mo, Si, Sb and Ca.
[0072] In some embodiments of the present invention, the A source is at least one of acetate, carbonate and basic carbonate containing A, and the A is at least one of Pb, Na, Sn, Sr, K, Ca, Ba, Ln, Pr, Sm, Gd and La.
[0073] In some embodiments of the present invention, the B source is at least one of acetate, carbonate and basic carbonate containing B, and the B is at least one of Ti, Mg, Y, Zn, Fe, Ta, Mn, Co, Ni, Mo, Nb, W and Al.
[0074] In some embodiments of the present invention, the mixed solution is an aqueous solution of source A and source B.
[0075] In some embodiments of the present invention, the molar ratio of element A to element B in the mixed solution is (1~1.1): (1~1.1).
[0076] In some embodiments of the present invention, the mixed solution is sprayed on the surface of the aluminum source and the positive electrode active material in a stirred state, and then dried to obtain a spray-coated positive electrode material.
[0077] In some embodiments, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide, and aluminum oxyhydroxide.
[0078] The invention adds an aluminum source for sintering together, which is beneficial to improving the cycle stability of the positive electrode material.
[0079] In some embodiments of the present invention, the stirring speed is 300-1500 r / min; In some embodiments of the present invention, the spraying time is 10 to 60 minutes; In some embodiments of the present invention, the drying temperature is 40-150° C., preferably 40° C.; the drying time is 0.5-3 h, preferably 0.5 h.
[0080] In some embodiments of the present invention, the sintering temperature is 350-700° C., preferably 550° C.; the sintering time is 2-10 h, preferably 4 h.
[0081] In some embodiments of the present invention, the crushing adopts at least one of a vibrating screen, a mechanical mill, and a jet mill.
[0082] In a third aspect, the present invention provides a positive electrode plate, the positive electrode plate comprising the positive electrode material obtained in any of the above embodiments. The positive electrode plate comprises a positive current collector and a positive active material layer, the positive active material layer comprising the positive electrode material provided in the first aspect of the present invention. The positive current collector can generally be a sheet body, the positive active material layer can generally at least partially cover the surface of the positive current collector, and can also be a layer body extending along the surface of the positive current collector. The positive current collector is generally a structure or part for collecting current, for example, it can be a metal foil (for example, copper foil, aluminum foil, etc.). Those skilled in the art can select a suitable method to prepare the positive electrode plate, for example, it can include the following steps: after the positive active material, binder, and conductive agent are mixed to form a slurry, it is coated on the positive current collector.
[0083] In a fourth aspect, the present invention provides a lithium-ion battery, comprising the positive electrode material provided in the first aspect of the present invention, or the positive electrode plate provided in the third aspect of the present invention.
[0084] The lithium-ion battery provided by the present invention may generally include a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte. The method for preparing the lithium-ion battery should be known to those skilled in the art. For example, the positive electrode sheet, the separator, and the negative electrode sheet may each be a sheet body, so that they can be cut into a target size and stacked in sequence, and can also be wound to a target size to form a battery cell, and can be further combined with an electrolyte to form a lithium-ion battery.
[0085] In the lithium-ion battery provided by the present invention, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer located on the surface of the negative electrode current collector, and the negative electrode active material layer generally includes a negative electrode active material. The negative electrode active material can be various materials suitable for negative electrode active materials of lithium-ion batteries in the art, for example, it can be a combination of one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium, etc. Among them, the graphite can be selected from a combination of one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material can be selected from a combination of one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material can be selected from a combination of one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is generally a structure or part that collects current, and the negative electrode current collector can be various materials suitable for use as a negative electrode current collector of lithium-ion batteries in the art, for example, the negative electrode current collector can be a metal foil, etc., more specifically, it can be a copper foil, etc.
[0086] In the lithium-ion battery provided by the present invention, the isolation membrane can be any material suitable for lithium-ion battery isolation membranes in the art, for example, it can be a combination of one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers, etc.
[0087] In the lithium-ion battery provided by the present invention, the electrolyte can be any electrolyte suitable for lithium-ion batteries in the art. For example, the electrolyte generally includes an electrolyte and a solvent. The electrolyte generally includes a lithium salt, etc. More specifically, the lithium salt can be an inorganic lithium salt and / or an organic lithium salt, etc. The lithium salt can be selected from a combination of one or more of LiPF6, LiBF4, LiN(SO2F)2 (abbreviated as LiFSI), LiN(CF3SO2)2 (abbreviated as LiTFSI), LiClO4, LiAsF6, LiB(C2O4)2 (abbreviated as LiBOB), and LiBF2C2O4 (abbreviated as LiDFOB). For another example, the concentration of the electrolyte can be between 0.8 mol / L and 1.5 mol / L. The solvent can be any solvent suitable for the electrolyte of lithium ion batteries in the art. The solvent of the electrolyte is usually a non-aqueous solvent, preferably an organic solvent, and specifically can include but is not limited to ethylene carbonate, propylene carbonate, butylene carbonate, pentyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, etc. or a combination of one or more of their halogenated derivatives.
[0088] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0089] Example 1 A method for preparing a positive electrode material comprises the following steps: (1) Preparation of positive electrode active material: The molar ratio of n(Li):n(Co):n(Ti):n(Al)=1.07:1:0.002:0.020 is used to weigh lithium carbonate, cobalt oxide, titanium oxide, and aluminum oxide, and mix them evenly. The mixture is sintered at 1020°C for 10 hours, and then crushed to obtain doped lithium cobalt oxide, which is the positive electrode active material with the chemical formula LiCo 0.9785 Ti 0.0020 Al 0.0195 O2.
[0090] (2) Preparing a mixed solution: Lanthanum acetate and aluminum nitrate were weighed and dissolved in deionized water at a molar ratio of n (La): n (Al) = 1:1 to obtain a mixed solution in which the total mass percentage of La and Al elements was 2%.
[0091] (3) Preparation of spray-coated positive electrode material: The positive electrode active material and alumina are placed in a high mixing device, premixed at 1000 r / min for 5 min to obtain a solid material, and the mixed solution is sprayed while stirring. The spraying is completed after 10 min, and then the material is mixed for another 5 min and then further dried at 40°C for 30 min to obtain a spray-coated positive electrode material; the mass of alumina is 0.2% of the mass of the positive electrode active material, and the feed ratio of solid material to mixed solution is 5 kg:400 mL.
[0092] (4) Preparation of positive electrode material: The spray-coated positive electrode material was placed in a box furnace and sintered at 550°C for 4 h. After crushing, it was passed through a 400-mesh sieve to obtain the positive electrode material.
[0093] Example 2 A method for preparing a positive electrode material comprises the following steps: (1) Same as Example 1.
[0094] (2) Preparation of a mixed solution: Sr(III) acetate and titanium(II) hydroxyacetate were weighed and dissolved in deionized water at a molar ratio of n(Sr):n(Ti)=1:1 to obtain a mixed solution containing 2% of the total mass percentage of Sr and Ti.
[0095] (3) Preparation of spray-coated positive electrode material: The positive electrode active material and alumina are placed in a high mixing device, premixed at 1500 r / min for 5 min to obtain a solid material, and the mixed solution is sprayed while stirring. The spraying is completed after 10 min, and then the material is mixed for another 5 min and then further dried at 40°C for 30 min to obtain a spray-coated positive electrode material; the mass of alumina is 0.2% of the mass of the positive electrode active material, and the feed ratio of solid material to mixed solution is 5 kg:400 mL.
[0096] (4) Same as Example 1.
[0097] Example 3 (1) Preparation of positive electrode active materials: Weigh lithium carbonate, NCM622 (Ni 0.6 Co 0.2 Mn 0.2 OH2), tungsten oxide, and aluminum oxide are uniformly mixed, sintered at 1020°C for 10 hours, and then crushed to obtain nickel-cobalt-doped lithium manganese oxide, which is the positive electrode active material with a chemical formula of LiNi 0.595 Co 0.198 Mn 0.199 W 0.0007 Al 0.0073 O2.
[0098] (2) to (4) are the same as in Example 1.
[0099] Example 4 (1) Same as Example 1; (2) Preparing a mixed solution: Lanthanum acetate and molybdenum nitrate were weighed and dissolved in deionized water at a molar ratio of n (La): n (Mo) = 1:1 to obtain a mixed solution in which the total mass percentage of La and Mo elements was 2%.
[0100] (3)~(4) are the same as in Example 1.
[0101] Example 5 (1) Same as Example 1.
[0102] (2) Preparing a mixed solution: Lanthanum acetate, calcium nitrate and yttrium nitrate were weighed and dissolved in deionized water at a molar ratio of n(La):n(Ca):n(Y)=0.5:0.5:1 to obtain a mixed solution with a total mass percentage of metal elements of 3%.
[0103] (3) Preparation of spray-coated positive electrode material: The positive electrode active material and alumina were placed in a high mixing device, premixed at 300 r / min for 5 min to obtain a solid material, and the mixed solution was sprayed while stirring. The spraying was completed in 60 min, and then the material was mixed for 5 min and discharged. The material was further dried at 150 °C for 30 min to obtain a spray-coated positive electrode material; the mass of alumina was 0.2% of the mass of the positive electrode active material, and the feed ratio of solid material to mixed solution was 5 kg:267 mL.
[0104] (4) Same as Example 1.
[0105] Example 6 (1) Same as Example 1.
[0106] (2) Preparing a mixed solution: Lanthanum acetate, calcium nitrate, yttrium nitrate and magnesium acetate were weighed and dissolved in deionized water at a molar ratio of n(La):n(Ca):n(Y):n(Mg)=1:1:1:1 to obtain a mixed solution with a total mass percentage of metal elements of 2%.
[0107] (3) Preparation of spray-coated positive electrode material: The positive electrode active material and alumina are placed in a high mixing device, premixed at 1000 r / min for 5 min to obtain a solid material, and the mixed solution is sprayed while stirring. The spraying is completed after 10 min, and then the material is mixed for another 5 min and then further dried at 40°C for 3 h to obtain a spray-coated positive electrode material; the mass of alumina is 0.2% of the mass of the positive electrode active material, and the feed ratio of solid material to mixed solution is 5 kg:400 mL.
[0108] (4) Preparation of positive electrode material: The spray-coated positive electrode material was placed in a box furnace and sintered at 700°C for 2 h. After crushing, it was passed through a 400-mesh sieve to obtain the positive electrode material.
[0109] Example 7 The difference from Example 1 is that the total mass percentage of metal elements in the mixed solution of step (2) is 4%, and the feeding ratio of solid material to mixed solution is 5 kg:200 mL.
[0110] Example 8 The difference from Example 1 is that the drying temperature in step (3) is 60°C.
[0111] Example 9 The difference from Example 1 is that the sintering temperature of step (4) is 350° C. and the sintering time is 4 h.
[0112] Example 10 The difference from Example 1 is that the sintering temperature in step (4) is 550° C. and the sintering time is 8 h.
[0113] Comparative Example 1 The difference from Example 1 is that source A and source B are not added, and the specific steps are as follows: (1) Same as Example 1.
[0114] (2) The positive electrode active material and alumina are placed in a high mixing device and mixed at 1000 r / min for 20 min to obtain a solid material, wherein the mass of the alumina is 0.2% of the mass of the positive electrode active material.
[0115] (3) Preparation of positive electrode material: The solid material was placed in a box furnace and sintered at 550°C for 4 h. After crushing, it was passed through a 400-mesh sieve to obtain the positive electrode material.
[0116] Comparative Example 2 The difference from Example 1 is that the A source and the B source are dry mixed with the positive electrode active material, and the specific steps are as follows: (1) Same as Example 1.
[0117] (2) The positive electrode active material and the dopant are mixed in a mass ratio of 5 kg:8 g, wherein the dopant is in a molar ratio of n A mixture of lanthanum oxide and aluminum oxide with a ratio of (La):n(Al)=1:1 is prepared, and then 0.2% of the mass of aluminum oxide of the positive electrode active material is added, and the materials are mixed at 1000r / min for 20min to obtain a spray-coated positive electrode material.
[0118] (3) Same as step (4) of Example 1.
[0119] Comparative Example 3 The difference compared with Example 1 is that no aluminum source is added. The specific steps are as follows: (1) Same as Example 1.
[0120] (2) Lanthanum acetate is dissolved in water to obtain an aqueous solution with a 2% by mass percentage of lanthanum element, thereby obtaining a lanthanum source solution.
[0121] (3) Use lanthanum source solution instead of mixed solution for spraying.
[0122] (4) Same as Example 1.
[0123] Comparative Example 4 The difference compared with Example 1 is that no lanthanum source is added, and the specific steps are as follows: (1) Same as Example 1.
[0124] (2) Aluminum nitrate is dissolved in water to obtain an aqueous solution with a mass percentage of 2% aluminum element, thereby obtaining an aluminum source solution.
[0125] (3) Use aluminum source solution instead of mixed solution for spraying.
[0126] (4) Same as Example 1.
[0127] Comparative Example 5 The difference compared with Example 1 is that the sintering temperature of step (4) is 900°C.
[0128] Comparative Example 6 The difference compared with Example 1 is that the drying temperature in step (3) is 300°C.
[0129] Comparative Example 7 The difference from Example 5 is that the A source and the B source are dry mixed with the positive electrode active material, and the specific steps are as follows: (1) Same as Example 5.
[0130] (2) The positive electrode active material and the dopant are mixed in a mass ratio of 5kg:8g, wherein the dopant is a mixture of lanthanum oxide, calcium oxide and yttrium oxide in a molar ratio of n(La):n(Ca):n(Y)=0.5:0.5:1, and 0.2% of the mass of the positive electrode active material is added with aluminum oxide, and the materials are mixed at 1000r / min for 20min to obtain a spray-coated positive electrode material.
[0131] (3) Same as step (4) of Example 5.
[0132] Comparative Example 8 The difference compared with Example 3 is that the mixed solution of source A and source B is not added.
[0133] Comparative Example 9 The difference from Example 3 is that the A source and the B source are dry mixed with the positive electrode active material, and the specific steps are as follows: (1) Same as Example 3.
[0134] (2) The positive electrode active material and the dopant are mixed in a mass ratio of 5kg:8g, wherein the dopant is a mixture of lanthanum oxide and aluminum oxide in a molar ratio of n(La):n(Al):=1:1, and 0.2% of the mass of the positive electrode active material is added with aluminum hydroxide, and the materials are mixed at 1000r / min for 20min to obtain a spray-coated positive electrode material.
[0135] (3) Same as step (4) of Example 3 Comparative Example 10 The difference from Example 5 is that in step (3), the positive electrode active material is dispersed in the mixed solution. The specific steps are as follows: (1) Same as Example 5.
[0136] (2) Lanthanum acetate, calcium nitrate, and yttrium nitrate were weighed and dissolved in deionized water at a molar ratio of n(La):n(Ca):n(Y)=0.5:0.5:1 to obtain a mixed solution with a total mass percentage of metal elements of 3%.
[0137] (3) The positive electrode active material and alumina were dispersed in the mixed solution, stirred for 30 min, and then stirred in an oil bath at 100°C and the solvent was evaporated to obtain a spray-coated positive electrode material; the mass of alumina was 0.2% of the mass of the positive electrode active material, and the total feed ratio of the positive electrode active material and alumina to the mixed solution was 5 kg: 267 mL.
[0138] (4) Same as Example 5.
[0139] The test of the present invention is as follows: (1) Electrochemical performance test: ① Preparation of pole pieces: positive electrode material, SP (conductive agent), PVDF (binder) are mixed in a mass ratio of 92:4:4, NMP (N-methylpyrrolidone) is added, stirred to form a slurry, coated on aluminum foil, and dried at 80°C to form a positive pole piece; graphite, SP (conductive agent), binder, and dispersant are mixed in a mass ratio of 95.5:1.5:1.5:1.5, water is added, stirred to form a slurry, coated on aluminum foil, and dried at 80°C to form a negative pole piece; ② Soft-pack battery assembly: Assemble the positive electrode sheet, negative electrode sheet, electrolyte and separator into a soft-pack battery; ③ Capacity test (25℃, 0.2C): At room temperature 25℃, charge at a constant current of 0.2C to V2 voltage, and further charge at V2 constant voltage condition until the current is lower than 0.05C, so that it is in V2 full charge state. Then discharge at a constant current of 0.2C to V1 to obtain the discharge capacity. The discharge gram capacity at 0.2C / 0.2C rate is obtained by the following calculation formula: discharge gram capacity = discharge capacity / mass of positive electrode material.
[0140] Among them, the V1 of lithium cobalt oxide positive electrode material is 3.0V, V2 is 4.48V, and the V1 of nickel cobalt manganese oxide lithium (Ni:Co:Mn=6:2:2) positive electrode material is 2.8V, V2 is 4.0V.
[0141] ④ Capacity retention test (45℃, 1.0C): The cycle capacity retention performance of the positive electrode material is evaluated by the number of cycles when the capacity drops to 80%; one cycle includes: the battery to be tested is charged to V2 at 1C constant current after standing for 120 minutes, and then charged to 0.05C at V2 constant voltage, and discharged to V1 at 1C constant current after standing for 5 minutes, and the discharge capacity is recorded; repeat the above steps until the battery capacity drops to 80%, and record the number of cycles; the battery capacity drops to 80% means that the ratio of the discharge capacity after n cycles to the discharge capacity in the first cycle is 80%.
[0142] Among them, the V1 of lithium cobalt oxide positive electrode material is 3.0V, V2 is 4.48V, and the V1 of nickel cobalt manganese oxide lithium (Ni:Co:Mn=6:2:2) positive electrode material is 2.8V, V2 is 4.0V.
[0143] ⑤ Storage gas production test: The battery to be tested is fully charged at 1C and then stored at 70°C. The battery is taken out regularly and cooled to room temperature to test the thickness of the battery. The growth of battery thickness at different storage times is calculated. The gas production of the positive electrode material is evaluated based on the growth of battery thickness. The test time period is 0, 7, 15, 30, 60, and 100 days. Taking 100 days as an example, the storage gas production rate of the positive electrode material on the 100th day can be calculated by the following formula: (H 100 -H0) / H0, where H 100 and H0 are the thickness of the battery measured on the 100th day and the 0th day, respectively.
[0144] (2) Transmission electron microscopy (TEM) test: The present invention uses a Thermo Fisher transmission electron microscope to observe and analyze the crystal structure of the positive electrode material.
[0145] (3) Scanning electron microscopy (SEM) test: The present invention uses a Nova NanoSEM 450 electron scanning electron microscope to observe and analyze the surface morphology of the positive electrode material.
[0146] (4) Particle size test: The Dv50 of the positive electrode material is tested using a laser particle size analyzer in accordance with GB / T 19077-2016.
[0147] (5) Repose angle test: Test the repose angle of the positive electrode material in accordance with GB / T 16913-2008.
[0148] Instructions attached Figure 1 , 2, 3, and 4 are SEM images of the positive electrode materials prepared in Examples 1 and 5 and Comparative Examples 1 and 10, respectively. It can be seen from the figure that since Comparative Example 1 is not mixed with source A and source B for surface coating modification, the surface of the positive electrode material particles is smooth and angular. Comparative Example 10 directly disperses the positive electrode active material in a mixed solution containing source A and source B and then obtains a spray-coated positive electrode material by evaporating the solvent. Therefore, the surface roughness of the obtained positive electrode material is relatively high, and the perovskite structure layer is mainly coated on the material surface in an island-shaped part, and the coating uniformity is poor; the particles of the positive electrode materials prepared in Examples 1 and 5 are smoother in shape than those in Comparative Example 1, indicating that the coating is successful; and compared with Comparative Example 10, the perovskite structure layer is mostly covered on the surface in a film-like state, which greatly reduces the surface roughness of the positive electrode material particles and the coating uniformity is relatively high.
[0149] Instructions attached Figure 5 This is the TEM image of the positive electrode material prepared in Example 5. It can be seen from the figure that the positive electrode material includes a four-layer structure, namely a layered structure, a substituted layered structure, a spinel / rock salt phase, and a perovskite structure, which correspond to a layered matrix, a substituted layered matrix layer, a heterojunction layer, and a perovskite structure layer, respectively; in addition, it can be seen from the figure that the thickness of the substituted layered matrix layer is less than 50nm, the thickness of the heterojunction layer is less than 10nm, and the thickness of the perovskite structure layer is less than 10nm.
[0150] The Dv50 of the positive electrode materials prepared in the embodiments of the present invention and the comparative examples are both 12~18μm; the repose angle of the positive electrode material prepared in the embodiments of the present invention is 25~55°, while the repose angles of comparative examples 2, 7, and 10 are 58°, 60°, and 57°, respectively. Among them, the positive electrode active materials of comparative examples 2 and 7 are dry-mixed with the oxides of source A and source B, and the positive electrode material of comparative example 10 is dispersed in a mixed solution containing source A and source B and then the solvent is evaporated to obtain a spray-coated positive electrode material. Compared with the spraying method of the present invention, the surface roughness of the positive electrode materials prepared by the two methods of the comparative examples (dry method, solution mixing) are higher, and therefore the repose angle is higher.
[0151] The properties of the positive electrode materials prepared in the embodiments and comparative examples are shown in Table 1 and Table 2, wherein Table 1 is the test results of the lithium cobalt oxide positive electrode materials, and Table 2 is the test results of the nickel cobalt manganese oxide lithium positive electrode materials.
[0152] Table 1: Lithium cobalt oxide cathode materials
[0153] Table 2: Nickel cobalt manganese oxide cathode materials
[0154] It can be seen from Table 1 that Example 1, Example 2, and Example 3 are surface-coated and modified, and have higher capacity and cycle stability, and lower gas production, while Comparative Example 1, which is not surface-coated and modified, has low cycle stability and significantly deteriorated gas production, indicating that surface coating and modification have a significant effect on improving the surface of the positive electrode material.
[0155] Comparing Example 7 with Example 1, increasing the concentration of the solute in the mixed solution, the capacity decreased, and the gas production slightly deteriorated; comparing Example 1, Example 9 and Example 10, reducing the sintering temperature or extending the sintering time, the capacity and cycle stability decreased slightly; after reducing the sintering temperature, the gas production deteriorated. Comparing Example 1 with Comparative Example 2, and Example 3 with Comparative Example 8, source A and source B were dry-mixed with the positive electrode material in the form of oxides, and the capacity, cycle stability and gas production were deteriorated, indicating that the wet spraying process is conducive to forming an effective coating modification layer to improve the capacity, cycle stability and gas production problems. Comparing Example 1, Comparative Example 3 and Comparative Example 4, it can be seen that the effect of coating modification using a single element is poor. Comparing Example 1, Comparative Example 5 and Comparative Example 6, it can be seen that the electrical performance tends to deteriorate when the sintering temperature and the drying temperature are increased.
[0156] In Comparative Example 10, the positive electrode active material is dispersed in a mixed solution containing source A and source B. With this mixing method, the degree of ion exchange between the positive electrode active material and the liquid phase is high, and the loss of lithium ions is large, resulting in a decrease in the capacity of the final positive electrode material, poor cycle stability and high gas production.
[0157] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes a layered matrix, a substituted layered matrix layer, a heterojunction layer, and a perovskite structure layer; the layered matrix has a chemical general formula Li a M 1-b M′ b O2, where 0.98 ≤ a ≤ 1.02, 0 < b ≤ 0.1, M is at least one of Ni, Co, and Mn; M′ is at least one of Ba, La, Ti, Zr, V, Nb, Cu, Mg, B, Sr, Al, Sc, Y, Ga, Zn, W, Mo, Si, Sb, and Ca; The substituted layered matrix layer is distributed in a direction away from the layered matrix and connected to the layered matrix, and the substituted layered matrix layer has a layered structure different from that of the layered matrix; The heterojunction layer is distributed on the surface of the substituted layered matrix layer away from the layered matrix, and is connected to the substituted layered matrix layer, and the heterojunction layer includes at least one of a spinel structure and a rock salt phase structure; The perovskite structure layer is distributed on the surface of the heterojunction layer away from the layered matrix and is connected to the heterojunction layer. The perovskite structure layer has a general chemical formula ABO3, wherein A and B are both metal elements.
2. A positive electrode material according to claim 1, characterized in that: The repose angle of the positive electrode material is ≤55°.
3. A positive electrode material according to claim 1 or 2, characterized in that: A is at least one of Pb, Na, Sn, Sr, K, Ca, Ba, Ln, Pr, Sm, Gd and La; B is at least one of Ti, Mg, Y, Zn, Fe, Ta, Mn, Co, Ni, Mo, Nb, W and Al; or / and, the total mass of the element A and the element B in the positive electrode material is less than 5% of the total mass of the positive electrode material; Or / and, the median particle size Dv50 of the positive electrode material is 12-18 μm; or / and, the thickness of the substituted layered matrix layer is less than 50 nm; or / and, the thickness of the heterojunction layer is less than 10 nm; Or / and, the thickness of the perovskite structure layer is less than 10 nm.
4. The method for preparing the positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Prepare positive electrode active material; prepare mixed solution of source A and source B; Spraying the mixed solution on the surface of the positive electrode active material in a stirred state, and obtaining a spray-coated positive electrode material after drying; The spray-coated positive electrode material is sintered and then crushed to obtain the positive electrode material.
5. The method for preparing the positive electrode material according to claim 4, characterized in that: The preparation method of the positive electrode active material comprises the following steps: mixing a lithium source, an M source and an M′ source, calcining the mixture, and crushing the mixture to obtain the positive electrode active material; The calcination temperature is 600-1100°C and the calcination time is 5-15h; Or / and, the lithium source is at least one of lithium carbonate, lithium hydroxide, lithium acetate and lithium oxalate; Or / and, the M source is at least one of an oxide or hydroxide containing M; the M is at least one of Ni, Co and Mn; Or / and, the M′ source is at least one of oxides, hydroxides, acetates, carbonates and basic carbonates containing M′; and the M′ is at least one of Ba, La, Ti, Zr, V, Nb, Cu, Mg, B, Sr, Al, Sc, Y, Ga, Zn, W, Mo, Si, Sb and Ca.
6. The method for preparing the positive electrode material according to claim 4, characterized in that: The A source is at least one of acetate, carbonate and basic carbonate containing A, and the A is at least one of Pb, Na, Sn, Sr, K, Ca, Ba, Ln, Pr, Sm, Gd and La; Or / and, the B source is at least one of acetate, carbonate and basic carbonate containing B, and the B is at least one of Ti, Mg, Y, Zn, Fe, Ta, Mn, Co, Ni, Mo, Nb, W and Al; Or / and, the mixed solution is an aqueous solution of source A and source B; Or / and, the molar ratio of element A to element B in the mixed solution is (1~1.1): (1~1.1).
7. The method for preparing the positive electrode material according to claim 4, characterized in that: The mixed solution is sprayed on the aluminum source and the surface of the positive electrode active material in a stirring state, and after drying, a spray-coated positive electrode material is obtained.
8. The method for preparing the positive electrode material according to any one of claims 4 to 7, characterized in that: The preparation method meets at least one of the following characteristics: Or / and, the stirring speed of the stirring is 300-1500 r / min; Or / and, the spraying time is 10 to 60 minutes; Or / and, the drying temperature is 40-150°C and the drying time is 0.5-3h; Or / and, the sintering temperature is 350-700° C. and the sintering time is 2-10 hours.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode material described in any one of claims 1 to 3.
10. A lithium ion battery, characterized in that: It comprises the positive electrode sheet, negative electrode sheet, electrolyte and isolation membrane as described in claim 9.
Citation Information
Patent Citations
Nano-engineered coatings for anode active materials, cathode active materials, and solid-state electrolytes and methods of making batteries containing nano-engineered coatings
CN107851840A
Modified positive electrode material and preparation method thereof, positive electrode plate, secondary battery and electric device
CN116960299A
Modified lithium ion battery positive electrode material, preparation method thereof and lithium battery
CN117133919A
Core-shell structure electrode catalyst with high activity and high stability
CN118448658A
Water-based slurry production with cathode active material coated with a solid electrolyte, production of an electrode from it and production of a lithium-ion battery cell
DE102018219589A1